Research on Revenge : A Research Note - Sakshi, Shivam; Shankar R., Sabari (Indian Journal of Marketing, 2022)
The pandemic has marked huge challenges and changes in the marketing contexts across all industries. Corporate organizations are at the outset to conceive marketing strategies to address the evolving, perhaps critical consumer behaviour — revenge shopping in the marketspace and marketplace. Though this form of shopping emerged decades ago, the nature of the shopping pattern in these pandemic times has a distinct set of motives being witnessed among consumers. Accordingly, the research evidence in this arena is not adequately bestowed that contributes to marketing implications. Hence, this research note has been proposed to indicate the key perspectives of research possibilities in the arena of revenge shopping. Though the requirements of research outcomes are unexceptionally pondered, the most critical perspectives, such as marketing strategy, the role of hedonism, and the viability of the structural relationship between revenge shopping, consumer satisfaction, consumer engagement and loyalty, have been analyzed and inferred as research notes. The implications, primarily on the research perspectives, have been pointed out for the researchers’ fraternity. The marketing implications have also been provided parallelly.